An Atom Probe with Ultra-Low Hydrogen Background. (August 2022) - Felfer, Peter; Ott, Benedict; Monajem, Mehrpad; Dalbauer, Valentin; Heller, Martina; Josten, Jan; Macaulay, Chandra
Abstract: Abstract : Atom probe tomography (APT) is a single-ion sensitive time-of-flight mass spectrometry method with near-atomic spatial resolution. In principle, it can be used to detect any chemical element, but so far hydrogen in the form of protium ( 1 H) had to be largely excluded. This is owing to the residual H emitted from the stainless-steel chambers and in-vacuum parts commonly used in atom probe instrumentation. This residual H is then picked up in the APT experiment. In this paper, we show that by replacing the stainless-steel chamber and in-vacuum parts with titanium parts, this residual H can largely be removed, thus enabling the direct imaging of H using APT. We show that besides the drastic reduction of H, also other contaminants such as O, OH, and H2 O are reduced by employing this instrument. In the current set-up, the instrument is equipped with high-voltage pulsing limiting the application to conductive materials.